Culture of Peace and Artistic Expressions With Persons Deprived of Liberty in the Institutional Attention Center Calle Real (Liberia) and the Semi-institutional Center (Nicoya) - Chavarría López, Doriam (2019)
The project presented below is a complement to the process of building a culture of peace within prisons, whose actions to be carried out in a pedagogical, formative, and practical way are aimed at strengthening one’s own knowledge and social behavior, through activities based on artistic techniques based on the language of movement. What is sought is that people deprived of freedom have a greater awareness of the importance of their role as individuals and as individuals within society, by enabling a better resolution of the problems they will face once they reintegrate into society. Through workshops, talks and artistic presentations, and through reflection and awareness of everyday situations, it is intended that, as human beings, the participants form part of socialization processes and social constructions in which they must comply with ideal models of being. Through integration, participation, communication, and corporal expression, people deprived of liberty would improve their perception of themselves and generate alternative ways of reflecting on problems and their resolution; all this, through the process of empowerment that is promoted in the participants from the ludopedagogy, which strengthens the process towards a culture of peace.